The Role of Bone Scintigraphy on Diagnosis of Torture - Ünüvar, Ümit; Dokudan, Erenç Yasemin; Yılmaz, Deniz; Kutlu, Levent; Özkalıpçı, Önder; Fincancı, Şebnem Korur (The Bulletin of Legal Medicine, 2016)
Although international human rights and humanitarian law consistently prohibit torture under any circumstance, torture that is a human crime is practiced all over the world. Torture is one of the most common forms of human rights abuse in countries with a history of military coups such as Turkey. Thousands of people were affected and the whole community from generation to generation has been deeply traumatized. Documentation of medical evidence is a very important step in the prevention of torture. Istanbul Protocol gives international standards for documentation of torture.The challenges to prove of medical evidence of torture in people who were suffered from torture many years ago, and/ or when the radiological methods failed to detect any occult injuries; some advanced methods such as bone scintigraphy were tested for diagnostic method. In this study, Human Rights Foundation of Turkeys applicants’ data were evaluated. The aim is to show to value of bone scintigraphy as a diagnostic method of torture and the results were discussed with literature.From 1991 to 2012, among of 13477 applicants of to HRFT’s Treatment and Rehabilitation Centers, totally 415 patients’ files that included bone scintigraphy scans were enclosed in this study. The patients files were evaluated retrospectively; and sex, age, socioeconomically status, torture methods, time since torture, duration of exposure to torture, physical and scintigraphy findings were documented. All of the patients reported repetitive and severe beatings and various forms of torture methods. 65 were female (15.7%), 350 were male (84.3%), mean age was 30.98 ±9.67 (range 11-72 year). 232 cases (56% of 415 cases) were scintigraphy positive and these results were consisted with the literature, and the detectable bone lesion on scintigraphy increased significantly with the duration of exposure to torture (7 days and more).Bone scintigraphy should be considered as a valuable non- invasive diagnostic method to evaluate and document traumatized patients with no detectable marks upon physical examination.Key words: Torture; Bone Scintigraphy; Documentation of Torture; Diagnostic Method; Istanbul Protocol.
Keywords: torture; bone scintigraphy; documentation of torture; diagnostic method; Istanbul protocol